2007
DOI: 10.1007/s00438-007-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

A shifted repertoire of endocannabinoid genes in the zebrafish (Danio rerio)

Abstract: The zebrafish has served as a model organism for developmental biology. Sequencing its genome has expanded zebrafish research into physiology and drug-development testing. Several cannabinoid pharmaceuticals are in development, but expression of endocannabinoid receptors and enzymes remains unknown in this species. We conducted a bioinformatics analysis of the zebrafish genome using 17 human endocannabinoid genes as a reference set. Putative zebrafish orthologs were identified in filtered BLAST searches as rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 53 publications
0
29
0
5
Order By: Relevance
“…This requirement made taxon sampling a challenge. PTPN22, for example, may be limited to amniotes -no PTPN22 ortholog was identified in the Tr genome, or in the zebrafish (Danio rerio), pufferfish (Tetraodon nigroviridis), and medaka (Oryzias latipes) genomes, as previously reported (McPartland et al, 2007). Species sampling limited to amniotes, however, did not provide adequate divergence for CB1, DAGLα, and MAGL phylograms, whose sequences are highly conserved (all branch length correlations were significant, data not shown).…”
Section: Mirrored Phylogramsmentioning
confidence: 45%
See 2 more Smart Citations
“…This requirement made taxon sampling a challenge. PTPN22, for example, may be limited to amniotes -no PTPN22 ortholog was identified in the Tr genome, or in the zebrafish (Danio rerio), pufferfish (Tetraodon nigroviridis), and medaka (Oryzias latipes) genomes, as previously reported (McPartland et al, 2007). Species sampling limited to amniotes, however, did not provide adequate divergence for CB1, DAGLα, and MAGL phylograms, whose sequences are highly conserved (all branch length correlations were significant, data not shown).…”
Section: Mirrored Phylogramsmentioning
confidence: 45%
“…A NAAA ortholog from Bos taurus, another laurasiatherian, was substituted for the missing Cf ortholog so the root of the Euarchontoglires branch could be determined, but the branch leading to Bos taurus was excluded in analyses. FAAH2 orthologs did not occur in several mammalian genomes (McPartland et al, 2007), so no FAAH2 phylogram was constructed. Sequence accession numbers are provided in Supplementary online Table 2 The use of cladistic approaches made it possible to investigate ancestral branches; we calculated branch lengths from five ancestral sequences, estimated from internal nodes in gene trees: primate (ancestor of Hs and Mamu), murid (ancestor of Rn and Mm), Euarchontoglires (ancestor of primate and murid), Mammalia (ancestor of Euarchontoglires and Cf), and amniote (ancestor of Mammalia and Gg).…”
Section: Mirrored Phylogramsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is worth noting evidence for cannabinoid receptors in vertebrates in addition to CB1 and CB2, such as the orphan receptor GPR55 [McPartland et al, 2007a;McPartland et al, 2007b], which has been identified as a novel cannabinoid receptor with ligand-binding and signaling properties partly similar to and partly unique from CB1 and CB2 [Pertwee, 2007;Ryberg et al, 2007;Lauckner et al, 2008]. Interestingly, AM-251, an analog of the CB1-selective antagonist SR141716 [Palmer et al, 2002], is a potent agonist for human GPR55 [Ryberg et al, 2005;Ryberg et al, 2007] and functions as a CB receptor agonist, mimicking the inhibitory effects of AEA and THC on fertility of sperm in the sea urchin S. intermedius [Berdyshev, 1999].…”
Section: Phylogeny Of the Endocannabinoid Systemmentioning
confidence: 99%
“…They regulate gene expression by binding to PPAR response elements (PPREs) as a heterodimer with RXR. In silico analysis showed that the zebrafish genome contains five genes encoding PPARs: duplicate PPARα and PPARβ genes and a single gene for PPARγ (Bertrand et al 2007, McPartland et al 2007, Den Broeder et al 2015. Studies on PPREs in the promoter regions of zebrafish fatty acid-binding protein (fabp) genes showed that different PPAR isoforms activate specific target genes (Laprairie et al 2016).…”
Section: The Zebrafish Peroxisome Proliferatoractivated Receptors (Ppmentioning
confidence: 99%